Odpowiedzi

  • Użytkownik Zadane
2010-03-13T22:37:41+01:00
A₅=a₃q²
54=6q²
q²=9
q=3 lub q=-3
a₃=a₁q²
6=a₁9
a₁=⅔
an=⅔q⁴
2010-03-13T22:39:13+01:00
A5/a3=q²
54/6=q²
9=q²
q=3 v q=-3

a3=a1q²

6=a1*3² v 6=a1*(-3)²
w obu wypadkach wychodzi
6=a1*9
a1=6/9=⅔

an=a1*q^n
an=⅔*3^n-1 lub an=⅔*(-3)^n-1
2010-03-13T22:41:59+01:00
A3 = 6
a5 = 54
a5 = a3*q² ---> q² = a5 : a3 = 54 : 6 = 9
q = √9 = 3 ∨ q = - 3
a3 = a1 *q² ---> a1 = a3 : q² = 6 : 9 = 2/3
a1 = 2/3
an = a1*q^(n-1)
Odp.
an = (2/3)*3^(n-1) ∨ an = (2/3)*(-3)^(n-1)